Estimates of genetic parameters for stayability and their associations with traits of economic interest in Gir dairy cows - Silva, R. M. O. [UNESP]; Boligon, A. A. [UNESP]; Fernandes, A. R.; Vercesi Filho, A. E.; El Faro, L.; Tonhati, H. [UNESP]; Albuquerque, L. G. [UNESP]; Fraga, A. B. (Funpec-editora, 2016)
The objective of the present study was to estimate genetic parameters for stayability at 60 months of age (STAY60) and its association with first lactation cumulative milk yield (P305), age at first calving (AFC), and first calving interval (FCI), in order to adopt these traits as selection criteria for longevity in Gir dairy cattle. Records for 2770 cows born between 1982 and 2008 from six herds in the Brazilian states of Minas Gerais, Sao Paulo, and Paribia were analyzed. The (co) variance components were estimated by a Bayesian approach using bivariate animal models. The heritability estimates were 0.37 +/- 0.09, 0.23 +/- 0.04, 0.26 +/- 0.06, and 0.07 +/- 0.03 for STAY60, P305, AFC, and FCI, respectively. The genetic correlations of STAY60 with P305, AFC, and FCI were moderate to high, with values of 0.61 (0.17), -0.44 (0.23), and 0.88 (0.13), respectively. STAY60, P305, and AFC exhibited additive genetic variability, and these traits should be considered in selection indices. The indirect selection for longevity through the correlated responses of early-expression traits, such as milk production at first lactation, could be used to improve the ability of animals to remain in the herd.
Keywords: Age at first calving; Genetic parameter; Longevity; First calving interval